E-Commerce And Social Media For Improving Business Performance - Hasminidiarty, Bunga Aditi, Ayu Sartika Pane, , Muller Tamba, Sopi Pentana (Program Pascasarjana STIE Amkop Makassar, 2023)
Problems with maintaining business performance, such as sales or profit levels, have been identified as a result of digital transformation. The post-pandemic situation continues to present barriers, preventing corporate actors from fully restoring sales to pre-pandemic levels. The presence of new enterprises is becoming more prevalent, creating competition among business actors. This condition has a negative impact on performance. Micro, small, and medium-sized enterprises (MSME) are one of the transformation priorities since they are important drivers of national economic stability, including the development of MSMEs in Medan City. The goal of this research is to determine and analyse the impact of e-commerce, social media, and digital transformation on business performance, in line with the expansion of the internet and its potential application for corporate development. A purposive sampling technique was utilised to choose MSMEs (n=121) in Medan City, with a focus on food and beverage, fashion, and automotive sectors. As an idea, the Medan City Government might help with digital transformation by utilising e-commerce and social media. The expansion of digital ecosystems such as e-commerce, social media, and digital transformation complements local economic growth, values community empowerment in MSMEs, and values local cultural expertise. This collaboration is in keeping with the ideals of sustainable development. Keywoard: digital transformation, e-commerce, Social media, business performance, MSMes